Can vacuum cleaning recover the infiltration capacity of a clogged porous asphalt? - Al-Rubaei, Ahmed; Stenglein, Anna Lena; Blecken, Godecke-Tobias; Viklander, Maria (Luleå tekniska universitet, Arkitektur och vatten, 2012)
Objective: The main threat for the performance of porous asphalt is clogging leading to decreased infiltration capacity. Thus, we investigated the potential of vacuum cleaning to recover the infiltration capacity of clogged permeable asphalts which have been in use for several decades. The influence of road operation and maintenance measures on the results was discussed.Method: We investigated the hydraulic conductivity (HC) of two roads with porous asphalt in Haparanda and Luleå, Sweden, which had been in use for 28 years and 15 years, respectively. A lack of appropriate maintenance during their operating life had lead to significant clogging and thus malfunction. The roads were vacuum cleaned using a vacuum cleaner/sweeping truck combination. This technology is recommended as a maintenance option for porous asphalt. Before and after the vacuum cleaning, replicate HC measurements were conducted using double-ring infiltrometers.Result: Before vacuum cleaning, mean HC was <0.1mm/min in Haparanda and between 0.4 and 0.8 mm/min in Luleå. After vacuum cleaning, HC increased significantly in Luleå (between 1.1 and 7.1mm/min) while no significant increase was detected in Haparanda. Despite the improvement after vacuum cleaning, HC was still far lower than the initial HC after construction. Reasons for the different results in Haparanda and Luleå were identified; the road winter maintenance was of primary importance.Conclusion: Depending on the extent of clogging, vacuum cleaning has the ability to recover HC of porous asphalt. However, long term behaviour of the HC depends largely on the street maintenance, thus regular appropriate maintenance is preferable. Godkänd; 2012; Bibliografisk uppgift: CD-ROM; 20120619 (andbra)